PENGARUH FERMENTASI MENGGUNAKAN KULTUR KOMBUCHA TERHADAP TINGKAT KEASAMAN DAN KADAR KAFEIN PADA EKSTRAK AIR BIJI KOPI HIJAU ROBUSTA (Coffea cenephora L.) DAN DAUN TEH HIJAU (Camellia sinensis (L.) Kuntze) - Susianah
Generally, coffee is consumed in form of powder of roasted coffee beans, while tea was commonly consumed which were from green tea leaves, oolong tea and black tea. However, nowadays there is a new way to drink coffee and tea in form of Kombucha Coffee (KC) and Kombucha Tea (KT), which are fermented liquid extract using Kombucha culture. One of the components of Kombucha culture is acetic acid bacteria. Bacteria and yeast are known for their ability to degradate caffeine. This study aimed to determine the influence of incubation time on level of acidity and caffeine content in KC and KT. Liquid media are made from 0.25 g green coffee beans powder or 0.25 g green tea leaves powder extract in 100 mL water, added by 10 g sucrose and 10 mL fermented liquid coffee and tea. Incubation carried out at 32 °C, not be shaken and not be moved. Incubation times used were 0, 6, and 12 days, then pH value was analyzed by pH meter and caffeine content was analyzed by High Performance Liquid Chromatography (HPLC). The system of HPLC was C-18 column, 5 ?m pore size, mobile phase methanol-water (7:3), and in flow rate of 1,0 mL/minute. The initial pH value of pure green coffee bean extract was 7.26, after adding fermented liquid coffee became 3.38, then after fermentation for 6, and 12 days became 2.74 and 2.42, respectively. The initial pH value of pure green tea leaves extract was 6.50, after adding fermented liquid tea became 3.50, then after fermentation for 6 and 12 days became 2.79 and 2.70, respectively. While the initial caffeine content in pure green coffee bean extract was 6.19, after adding fermented liquid coffee became 5.83, then after fermentation for 6 and 12 days became 4.62 ± 0.21 and 2.96 ± 0.13 mg/L, respectively. The initial caffeine content in pure green tea leaves extract was 11.01, after adding fermented liquid tea became 9.49, then after fermentation for 6 and 12 days became 8.70 ± 0.03 and 8.12 ± 0.14 mg/mL, respectively. The longer incubation time, should the lower pH value and caffeine content in KC and KT, at least after 12 days fermentation.